The Relationship between Selected Factors of Rating Dissatisfaction and Employees’ Satisfaction on the Appraisal Decisions - Rusli, Ahmad; Lydia, Paya; Ali, Baig; Nur Naha, Abu Mansor; Wan Khairuzzaman, Wan Ismail (International Journal Of Innovation And Business Strategy, 2012)
This study aims to determine the relationship between selected factors of rating dissatisfaction and employees’ satisfaction on the appraisal decisions. The factors of rating dissatisfaction that examine in this study are including raters’ attitude, rater’s error, halo effect, recency effect. This study used positivism as a research philosophy and quantitative methodology was used to examine the relationship between independent variables and dependent variables involves. A cross - sectional survey was used to collect data from different groups of respondents at from a variety of personnel departments in different categories of works in broadcasting agency, Sarawak, Malaysia. Questionnaire was the research instrument used in this study to collect data. Validity and reliability issues of the instrument were taken care by conducting the best practice goodness of data preparation. 150 sets of the questionnaires were distributed and only 130 completed sets of the questionnaires were successfully collected and used for further analysis. The data that collected were analyzed through Statistical Package for Social Sciences (SPSS) version 14.5. Descriptive statistic used to explain the demographic characteristics of respondents. Pearson Correlation Analysis used to identify the relationship between the selected variables involves. The findings of this study have shown that raters’ attitude, recency effect and deflation of marks are significantly related to dissatisfaction among employees in performance appraisal decisions. Based on the findings of the study, the top management of departments can gain some insight into their employees’ satisfaction of their performance appraisals decisions. It is recommended that there is a need for more transparent performance appraisal processes and more professional roles of the raters in performing their job. This study contributes significantly to the body of knowledge, human resource practitioners, policy makers and others interested parties on issues pertaining to the relationship between job satisfaction and job performance. Implications and recommendations for future research have also been put forth in this paper.